Pengaruh Waktu Tinggal dan Umur Tanaman pada Biosorpsi Ammonia oleh Tanaman Air Enceng Gondok (Eichhornia Grassipes) - Suhendrayatna, Suhendrayatna; Bahagia, Bahagia; Novia, Novia; Elvitriana, Elvitriana (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2009)
Ammonia biosorption by using Enceng Gondok, Eichhornia crassipes, was conducted in outdoor laboratory with objective to study the influence residence time and plant age to ammonia biosorption rate. The research uses reactor test consisting of wet land and sludge. Enceng Gondok is planted on reactor test flown by ammonia as bacth with relatif low enough concentration (2 mg/L), water height 20 cm, plants number in each reactor of 4 stems with variatious plants length 10, 20, 30, and 40 cm, and various residence time 2, 4, 6, and 8 days. Each test conducted was completed by controlling reactor. Research result showed that maximun biosorption occurs at 2 days culturization; ammonia biosorption rate by roots increases as residence time increases. Residence time 2, 4, 6 and 8 days can decrease ammonia concentration up to 1.568 mg/l, 0.245 mg/l, 0.204 mg/l (10%), and 0.022 mg/l, respectively, at plant length 10 cm. Further, research results showed that the more the plants age, the larger the biosorption by plant.Keywords: ammonia biosorption, enceng gondok, plants age, residence time